The educational background of the Top Managers of the Italian Health Authorities: results of a study on eight Regions - Rossi, Deanna; Bizzarro, Assunta; Affanni, Paola; Pasquarella, Cesira; Odone, Anna; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2019)
A survey to investigate the educational background of the Health Top Managers recently appointed by Italian Regions as CEOs (Chief Executive Officer) of Local Health Authorities (ASL) and General Hospitals was performed in April 2019, approximately one year after the entry into force of the new law for their selection (D.Lgs 171/2016). The study follows a similar one carried out by Bocconi University in 2013 and focuses on 8 Italian Regions (Piedmont, Lombardy, Liguria, Umbria, Lazio, Basilicata, Sicily, Sardinia). The study examined the CVs of the 112 recently appointed CEOs: the average age is 58.7 years, with the proportion of female surprisingly low (16%). About half of them (50.5%) have a Degree in Medicine and Surgery. Among Managers with a non-medical degree (49.5%), Law (21) and Economic sciences (21) are the most common degrees. Among medical doctors, 33 (58.9%) are specialists in Hygiene and Preventive Medicine. Overall, our data are consistent with those recorded in 2013 (except a decrease in medical graduates -18.5%) and confirm the diversified backgrounds of Health Managers. The background in Public Health, acquired from the 35 Schools of Hygiene and Preventive Medicine, remains relevant among Managers of the Italian National Health Service.